Inclusões Dinâmicas em Escalas Temporais: Existência de Soluções sob a Hipótese de Semicontinuidade Inferior - Silva, Geraldo Nunes [UNESP]; Santos, Iguer Luis Domini dos; Barbanti, Luciano [UNESP] (Brazilian Society for Computational and Applied Mathematics (SBMAC), 2012)
In this paper we consider the problem of differential inclusion in time scales whose vector field is a multifunction, that is, a function that maps points to sets. It is provided conditions of existence without requiring compactness of the vector field; it is required that the vector field is closed, convex, and lower semicontinuous. In previous work in literature, it is required that the field is either scalar or compact, convex, and has closed graph.

Neste trabalho onsideramos o problema de in lusão diferen ial em es- alas temporais ujo ampo vetorial é uma multifunção, ou seja, uma função que mapea pontos a onjuntos. O trabalho forne e ondições de existên ia sem exigir ompa idade do ampo vetorial; exige apenas que ele seja onvexo, fe hado e semi- ontínuo inferior. Em trabalhos anteriores na literatura, ou o ampo é es alar ou exige-se que este, além de onvexo, seja ompa to e tenha o gráfico fe hado.
Keywords: inclusions in time scales; dynamic inclusions; existence of solutions